Disseminated BCGosis complicated by robust immune reconstitution in a child with severe combined immunodeficiency during transplant: A case report - N.S. Thillai Arunachalam; Dhaarani Jayaraman; Adarsh Kancharla; T.K. Shruthi; Swati Kumari; Rajeev Pulimi; Julius Xavier Scott (Elsevier, 2023)
Background: Patients with primary immunodeficiency disease (PID) are not only vulnerable to mycobacterial disease, but are also more likely to develop adverse events following BCG vaccination, including regional disease (BCGitis) to disseminated disease (BCGosis). Observations: A 7-month-old girl with severe combined immunodeficiency (SCID) presented with an erythematous tender swelling in left deltoid region while she was undergoing haplo-identical hematopoietic stem cell transplant (HSCT). She had an exuberant immune reconstitution syndrome with engraftment. Despite the odds, BCGosis was managed successfully with antituberculous therapy and symptomatic measures. Conclusion: BCGosis/BCGitis is a clinical challenge in children with PID, particularly during HSCT.